Autologous Bone Graft Versus Bone Morphogenetic Protein Augmentation for Comminuted Midshaft Femoral Fractures: A Systematic Review - Andika Prasetyo Arifin; M Yogi Alamsyah; Arimurti Pratianto; Rheza Fabianto Sebastian (Indonesian Journal Publisher, 2026)
Comminuted midshaft femoral fractures (AO/OTA 32-C2/C3) are complex injuries associated with extensive bone fragmentation, severe soft-tissue damage, and elevated risks of delayed union or nonunion. This systematic review, conducted in accordance with PRISMA guidelines, compared the efficacy and safety of autologous bone grafting (ABG) versus recombinant bone morphogenetic protein (BMP) augmentation as adjuncts to surgical fixation. Comprehensive searches of PubMed, Embase, and Cochrane databases identified twelve comparative studies involving patients treated with internal fixation plus biological enhancement. Primary outcomes included radiographic union rates, time to union, complications, functional recovery, and cost-effectiveness. Risk of bias was assessed using the ROBINS-I tool. Both ABG and BMP achieved high union rates (92% versus 90%), with BMP linked to an approximate two-week reduction in healing time. Substantial heterogeneity across studies, however, precluded definitive conclusions. ABG provided reliable results but was associated with donor-site morbidity in nearly one-fifth of patients. BMP avoided harvest-related complications yet increased risks of heterotopic ossification and soft-tissue edema while incurring significantly higher costs without proven superiority in preventing nonunion or reoperation. In conclusion, both ABG and BMP offer effective biological support for these fractures. Treatment selection should be individualized according to patient characteristics, fracture severity, complication profiles, and resource availability; routine BMP use is not currently justified.